2008
DOI: 10.1016/j.ejor.2007.08.017
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic for the container loading problem: A tertiary-tree-based dynamic space decomposition approach

Abstract: (2008). A heuristic for the container loading problem: A tertiary-tree-based dynamic space decomposition approach. European Journal of Operational Research, 191 (1) AbstractIncreasing fuel costs, post-911 security concerns, and economic globalization provide a strong incentive for container carriers to use available container space more efficiently, thereby minimizing the number of container trips and reducing socio-economic vulnerability. A heuristic algorithm based on a tertiary tree model is proposed to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…• CLP in its basic form in George and Robinson (1980), George (1992), Gehring (1998), Pisinger (2002), Moura and Oliveira (2005), Wang et al (2008), Parreño et al (2008a,b), Egeblad and Pisinger (2009), Huang and He (2009); • box grouping constraints in Bischoff and Ratcliff (1995); • weight distribution constraints in Gehring and Bortfeldt (1997), Davies and Bischoff (1999), Eley (2002); • stability and orientation constraints in Terno et al (2000), Bortfeldt and Gehring (2001), Gehring and Bortfeldt (2002), Bortfeldt et al (2003); • bearing strength constraints in Bischoff (2006). Wang et al (2008) well summarize the main available heuristics for the heterogeneous three-dimensional packing problem and provide a view of the advances in the use of intelligent heuristics (simulated annealing, tabu search and genetic algorithms).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…• CLP in its basic form in George and Robinson (1980), George (1992), Gehring (1998), Pisinger (2002), Moura and Oliveira (2005), Wang et al (2008), Parreño et al (2008a,b), Egeblad and Pisinger (2009), Huang and He (2009); • box grouping constraints in Bischoff and Ratcliff (1995); • weight distribution constraints in Gehring and Bortfeldt (1997), Davies and Bischoff (1999), Eley (2002); • stability and orientation constraints in Terno et al (2000), Bortfeldt and Gehring (2001), Gehring and Bortfeldt (2002), Bortfeldt et al (2003); • bearing strength constraints in Bischoff (2006). Wang et al (2008) well summarize the main available heuristics for the heterogeneous three-dimensional packing problem and provide a view of the advances in the use of intelligent heuristics (simulated annealing, tabu search and genetic algorithms).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al (2008) well summarize the main available heuristics for the heterogeneous three-dimensional packing problem and provide a view of the advances in the use of intelligent heuristics (simulated annealing, tabu search and genetic algorithms). Dychoff (1990) and Dyckhoff et al (1997) proposed a taxonomy for cutting and packing problems based on four criterion (dimensionality, kind of assignment, assortment of large objects and small objects).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rising fuel cost now provides a strong incentive for container carriers to maximize available container space, thereby minimizing the number of required trips across the global container transportation system [49]. The efficient loading of containers, that is, the minimization of empty spaces inside of them, is not only an economic requirement but also an ecological issue due to the adverse consequences of increased traffic on environmental resources [39].…”
Section: Introductionmentioning
confidence: 99%
“…90% of all cargo moves in containers and approximately 250 million are shipped annually (van de Voort et al 2003). At the moment, rising fuel costs provide strong incentive for container carriers to maximize available container space, thereby minimizing the number of required trips across the global container transportation system (Wang et al 2008). us, it can be concluded that the loading phase is one of the critical parts of the container shipment process.…”
Section: Introductionmentioning
confidence: 99%